The evolution of inflation and unemployment: explaining the roaring nineties - Marika Karanassou; Héctor Sala; Dennis J. Snower (Queen Mary University of London, Department of Economics, 2007)
This paper analyses the relation between US inflation and unemployment from the perspective of "frictional growth," a phenomenon arising from the interplay between growth and frictions. In particular, we examine the interaction between money growth (on the one hand) and various real and nominal frictions (on the other). In this context we show that monetary policy has not only persistent, but permanent real effects, giving rise to a long-run inflation-unemployment tradeoff. We evaluate this tradeoff empirically and assess the impact of productivity, money growth, budget deficit, and trade deficit on the US unemployment and inflation trajectories during the nineties.
Keywords: E51; E31; E24; E62; 330; Inflation dynamics; Unemployment dynamics; Phillips curve; Roaring nineties; Phillips-Kurve; New-Keynesian Phillips Curve; Theorie der Arbeitslosigkeit; Wirtschaftswachstum; Schätzung; USA